Culture medium and gastrointestinal environment positively influence the Saccharomyces cerevisiae RC016 cell wall polysaccharide profile and aflatoxin B1 bioadsorption - Fochesato, Analía Silvia (2020)
The objective was to study the influence of culture medium and gastrointestinal environment on Saccharomyces cerevisiae RC016 cell wall polysaccharides profile and the aflatoxin B1 (AFB1) adsorption. Probiotic Saccharomyces cerevisiae RC016, isolated from the pig small intestine, has previously shown efficient mycotoxins adsorption in vitro including AFB1. In addition, it was able to survive under the gastrointestinal (GI) tract conditions and did not cause in vitro and in vivo genotoxicity or cytotoxicity. In this work, transmission electron microscopy (TEM) was used to show ultrastructural variations in cell morphology and, infrared spectroscopy (IR-frequency range 4000–500 cm−1) was used to show variations in the spectra of yeast cells cultured in different culture media, Yeast extract Peptone Dextrose (YPD) medium and Dried distillers grains (DDG) medium (after passing the simulated GIT). The cell wall thickness in the DDG medium was the highest (68%-p≤0.0001). Infrared spectra had a similar spectral pattern for all treatments, however, bands from DDG medium had greater absorption intensity than those obtained from YPD and in turn, increased after the GI tract passage. S. cerevisiae RC016 showed important AFB1 adsorption in the simulated intestinal fluid (97.7% in DDG). The optimization of nutritional conditions coupled with the use of spectrophotometric tools allowed increasing, in a controlled manner, the main components of the cell wall responsible for adsorbing mycotoxins simulating the GI tract. Consequently, it could be possible to control the functional properties (probiotic and mycotoxin adsorbents) after scaling the yeast biomass production with low-cost substrates, allowing its effective application as a food additive.